Towards a framework for parenting programs for indigenous families in Australian metropolitan areas - Munns, Ailsa (Australian Association of Maternal Child and Family Health Nurses, 2010)
The aim of this descriptive literature summary is to summarise and review the literature related to parenting programs for Indigenous families in Australian metropolitan geographical areas and to provide recommendations to guide the development of community based clinical practice, guidelines and protocols. Information was sourced through CINHAL, Medline, Google Scholar, Science Direct, Informit and Scopus data bases from 2000 to 2010. Grey literature from government and non government organisations was accessed, along with information from the reference lists of accessed literature. The findings have demonstrated the need for culturally appropriate parent support programs for metropolitan Aboriginal families based on a primary health care framework and incorporating social determinants. Recommendations for program development and practice are identified.